2002
DOI: 10.1053/jhep.2002.35439
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with FK506 up-regulates insulin receptors in regenerating rat liver

Abstract: This report examines the effect of FK506 pretreatment on liver insulin receptor expression in partially (70%) hepatectomized rats. FK506 pretreatment led to an increased insulin receptor number 24 hours after hepatectomy, detected by means of insulin binding and crosslinking procedures. This increase was related to enhanced insulin receptor expression determined by in vitro mRNA translation and Western blot techniques. We also tested the functionality of the expressed insulin receptors by [ 3 H] thymidine inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…14,15,17,23 We found that pharmacological depletion of NK cells by anti-asialo GM1 treatment was sufficient for liver xeno-repopulation in Fah Ϫ/Ϫ Rag2 Ϫ/Ϫ mice. However, the level of xeno-repopulation was not comparable to those found in Fah…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…14,15,17,23 We found that pharmacological depletion of NK cells by anti-asialo GM1 treatment was sufficient for liver xeno-repopulation in Fah Ϫ/Ϫ Rag2 Ϫ/Ϫ mice. However, the level of xeno-repopulation was not comparable to those found in Fah…”
Section: Discussionmentioning
confidence: 87%
“…16 FK506 was also found to induce hepatocyte proliferation and promote liver regeneration in partial hepatectomized rats. 17 We tested the potential effect of FK506 on promoting liver xeno-repopulation in Fah Ϫ/Ϫ Rag2 Ϫ/Ϫ recipients, along with treatment of anti-asialo GM1. FK506 was administered to mouse recipients at a dose of 1 g/g body weight per day.…”
Section: Enhanced Level Of Liver Xeno-repopulation After Treatment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of FK506 played an important role by improving the efficiency of liver xeno-repopulation in Fah −/− Nod/Scid mice. In addition to immunosuppression, FK506 modulates liver responses by increasing the expression of local mitogens, such as insulin-like growth factor-I, and insulin receptors while, at the same time, decreasing the production of inhibitory cytokines such as interleukin 2, to promote liver regeneration [18][19][20]. FK506 reduces macrophage recruitment and attenuates leukocyte accumulation, neutrophil infiltration and the activation of resident immunocompetent hepatic NK cells [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…observaram que o tratamento com tacrolimus antes da ressecção de 70% do parênquima hepático em ratos adultos promove a regeneração por aumento da expressão dos receptores de insulina nos hepatócitos. 33 Considerando-se a importância do estudo dos efeitos das drogas imunossupressoras sobre a regeneração e remodelação do parênquima hepático em crianças submetidas a transplante de fígado, despertou-se o interesse pela pesquisa no animal de experimentação em crescimento, dadas as óbvias restrições éticas ao estudo em humanos. Por outro lado, do ponto de vista prático é inexeqüível a realização de transplante de fígado em animais de pequeno porte em crescimento, o que impossibilita a pesquisa com este modelo.…”
Section: (Figura 1)unclassified